Improving business performance of budget hotels through social media - Falcão, Roberto Pessoa de Queiroz; Castro, Andrea Ribeiro Carvalho de; Nascimento, Estefanie Silva do; Barboza, Tania da Silva; Ferreira, Jorge Brantes (REVISTA ACADÊMICA OBSERVATÓRIO DE INOVAÇÃO DO TURISMO, 2018)
The article aims at understanding how a hostel takes advantage of guests' opinions on digital social networks to improve their business performance. The budget-hospitality sector attracts younger and connected individuals that use social media as a decision-making tool for choosing their accommodation. On the other hand, some hotels already take advantage of customers’ feedbacks to improve service quality. The research is based on an exploratory single case study of a hostel chain in Brazil. Among the main findings, evidences point to how the hostel chain takes advantage of both eWOM and customer satisfaction surveys to improve its marketing performance and services, obtaining competitive advantages. In addition, social media is used as an important input for HR management, determining bonus criteria and team focus.